Using a videotaped objective structured clinical examination to assess Knowledge In Smoking cessation amongst medical Students (the K.I.S.S. Study). (1st December 2016) - Lucas, Nathanael C. C.; Walker, Natalie; Bullen, Chris
Abstract: Introduction: Brief smoking cessation advice from physicians is an effective smoking cessation intervention and is therefore an important skill medical students should master. We sought to assess the ability of medical students at the University of Auckland, New Zealand at different stages of their clinical education to provide accurate smoking cessation advice. Methods: Seventy-five medical students participated in a five-minute videotaped objective structured clinical examination (VOSCE) with a standardized patient. We marked them using a 10-point scale based on the "5As" of smoking cessation, with a score of 7/10 or more considered a pass. We used the general inductive method to analyze student feedback for key themes. Results: The mean score was 5.81/10, with only 15 (20%) students reaching the pass mark. Qualitative analysis revealed three themes: students had breadth of knowledge but lacked depth; their preference was to prescribe medications; and students were unable to identify where further smoking cessation support could be sourced. Discussion and conclusion: University of Auckland medical students performed poorly when giving smoking cessation advice. Inclusion of smoking cessation education in the undergraduate curriculum is required to ensure all graduates are capable of providing evidence-based and accurate cessation advice.